Impact Of Economic Freedom On Economic Development: A Nonparametric Approach To Evaluation - Andrea Vondrová; Elena Fifeková (European Scientific Journal, ESJ, 2016)
The paper examines the impact of economic freedom on economic development of European countries. Economic freedom is assessed using data from Heritage Foundation (Index of Economic Freedom). Nonparametric method - data analysis method is used which allows us to set a limit on the efficiency of the relationship between economic freedom and economic development. We assess to what extent the achieved degree of economic freedom in various countries is reflected in their level of economic performance, respectively what is the potential for better "assessment" of economic freedom to increase their economic level. The analysis confirmed that economic freedom creates better conditions for increasing economic performance. The decomposition of inefficiencies indicated that in the European transition economies there is a relatively strong area for improving economic performance through the extension of individual indicators of economic freedom.